Afrikaanse Bybelvertalings "vir Afrika". Die vertalers en hulle kulturele agenda - J. A. Naudé (Acta Theologica)
The purpose of the article is to indicate the ideological dominance of the Afrikaans target culture in Afrikaans Bible translations. This is measured by the way in which the Ancient Near Eastern and Ancient Mediterranean cultures of the source texts are domesticated. An analysis of nine Afrikaans Bible translations is provided in terms of commission and intention of the translation, the translation process (translator, source text, work method, translation method), and product of the translation. It is shown that the trend is to create translations that read fluently, i.e. the appearance that the translation is not in fact a translation, but the original.